Struktur Komunitas Zooplankton Pada Budidaya Ikan Koi (Cyprinus Rubrofuscus) dalam Sistem Vertiqua Menggunakan Biofical Fiter Atas - Zillan Zalila; Novita MZ; Neneng Nurbaeti (Habitat: Jurnal ilmiah ilmu Hewani dan Peternakan, 2024)
The zooplankton community structure in koi fish (Cyprinus rubrofuscus) aquaculture using the Vertiqua system with a biological biofilter was analyzed to understand the crucial role of zooplankton as an integral part of aquatic ecosystems. Zooplankton, which connects phytoplankton with carnivorous consumers, also serves as an effective biological indicator for assessing changes in aquatic environmental conditions. This study employed a descriptive method to observe the abundance and diversity of zooplankton in three Vertiqua ponds. The observations revealed that the zooplankton groups Rotifera and Ciliophora were dominant, with abundances of 118 Ind/l and 106 Ind/l, respectively. The three observed Vertiqua ponds were categorized as mesotrophic, with an average diversity index of 2.2, zooplankton evenness index of 0.7, and dominance index of 0.2. Measurements of the water’s physical-chemical factors showed an average temperature of 26°C, pH 6, DO 6 Mg/l, ammonia 0.05 Mg/l, nitrite 2.33 Mg/l, nitrate 14.6 Mg/l, and phosphate 1.1 Mg/l. Based on the abundance and diversity of zooplankton found, the pond water conditions can be categorized as mesotrophic with a moderate level of fertility, supporting a varied zooplankton community structure.